Digital Transformation Ushers in a New Era for the Insurance Industry (Journal of science and technology exploration, 2025)
Amid the global wave of digital transformation in the insurance industry, artificial intelligence technology is evolving from an auxiliary tool to core infrastructure, driving a profound paradigm revolution within the sector. Based on the agent theory framework, this paper systematically explains the application mechanisms of AI technology in key areas such as insurance business process re-engineering, product innovation, and risk management. By constructing an agent model of "Environmental Perception - Autonomous Decision-Making - Collaborative Execution - Continuous Evolution," it provides an in-depth analysis of the internal operational logic and development path of insurance agents. Research indicates that insurance agents, through four core processes—multi-source data perception, deep learning decision-making, automated execution, and continuous evolution—propel the industry's transformation from traditional experience-driven models to data-and-intelligence-driven ones. This paper conducts in-depth analyses of representative cases, including ZhongAn Insurance, Taikang Online, and Pacific Health Insurance, to validate the applicability and effectiveness of agent theory in insurance practice, offering both theoretical support and practical references for the industry's intelligent transformation. The study finds that AI technology not only significantly enhances the operational efficiency of insurance businesses but also exerts a profound impact on risk pricing, product innovation, and service experience. However, it simultaneously faces multiple challenges such as model reliability, data security, and ethical governance, necessitating the synergistic advancement of technological iteration, regulatory innovation, and organizational adaptation.
Keywords: Digital transformation; Artificial intelligence; Agent theory; InsuranceInsurance